2017
DOI: 10.1108/pr-03-2015-0077
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory foci and expatriate adjustment

Abstract: Purpose The purpose of this paper is to examine the relationship between regulatory foci and expatriate adjustment and further compares the differences in the aforementioned relationship between promotion focus and prevention focus. Design/methodology/approach This study adopts a convenient sampling method to survey expatriates who work for multinational enterprises and have been expatriated for at least six months. Findings Based on an analysis of 158 Taiwanese expatriates in Mainland China, Thailand, Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In the reliability analysis, Cronbach's α was selected in this article (Lee et al, 2017). The results showed that Cronbach's α values of all dimensions were greater than .7 (see Table 3), indicating good data consistency, which could be further analyzed.…”
Section: Reliability and Validity Analysismentioning
confidence: 99%
“…In the reliability analysis, Cronbach's α was selected in this article (Lee et al, 2017). The results showed that Cronbach's α values of all dimensions were greater than .7 (see Table 3), indicating good data consistency, which could be further analyzed.…”
Section: Reliability and Validity Analysismentioning
confidence: 99%
“…In determining the reliability of study instruments, Cronbach Alpha was adopted as parameter for measurement. A suitable and conventional reliability coefficient of any study must be equal to or greater than 0.70 (Lee et al, 2017). In the present study the reliability coefficient for sexual desire, sexual satisfaction and pain during virginal penetration are .94, .86, .91 respectively.…”
Section: Source: Field Work 2019mentioning
confidence: 69%
“…Regulatory foci were measured by a 12-item scale adopted from Wallace and Chen (2006), and which was supported by previous employees' studies of Hung, Huan, Lee, Lin, and Zhuang (2018) and Lee, Hung, Chien, Zhuang, and Hsu (2017). There are six items of promotion focus and six items of prevention focus.…”
Section: Regulatory Focimentioning
confidence: 99%